Pro WCF Practical Microsoft SOA Implementation - Peiris, Chris (Apress, 2012)
This book explains the Windows Communication Foundation (WCF) from the Service - Oriented Architecture (SOA) perspective. It explains WCF as an evolution of the SOA concept, not as a “message bus” concept built on the next generation of Microsoft products.